Historical Study of The Role of The Juang City: Bireuen For The Indonesian Independence Revolution Period - Muhjam Kamza; M Yusrizal; Mawardi Mawardi; Teuku Kusnafizal; Teuku Abdullah (Proceedings of AICS - Social Sciences, 2021)
The Aceh region became a battleground in the Dutch-Indonesian Revolutionary War of Independence, which lasted from 1945 to 1949. Bireuen, as one of Aceh's cities, became the core of the fight to stop the Dutch invasion of Indonesia. This research looks at the function of Bireuen, which has taken the jargon of "Kota Juang". The reference technique in this study is historical research utilizing a qualitative approach. The data was also gathered through a literature review, which included books, journals, and document reviews, as well as field observations, which included memoirs written by the offenders and historical witnesses in the occurrence. Bireuen has three primary functions following the completion of the study. First, the city of Bireuen served as the focal point for the military defensive equipment for the battle, which was gained as a result of the Japanese armory's spoils of war. The existence of the TNI Headquarters Division X in Bireuen as a command center for attacks against the Dutch in the Medan Area is the second reason. Three, the role of Radio Rimba Raya in international debunking of Dutch propaganda. This radio program begins by stating that Indonesia is an independent country and that Aceh is a part of the Republic of Indonesia's Unitary State. The Dutch recognized Indonesia's sovereignty as an independent country after three main roles and several supporting parts in the Indonesian Independence Revolution in Bireuen. On this premise, Bireuen is deserving of the nickname of "City of Fighting for the Independence Revolution".Keywords: Juang City, Independence Revolution, Independence Revolutionary War.